Real-time systems development with RTEMs and multicore processors - Bloom, Gedare; Sherrill, Joel; Hu, Tingting; Bertolotti, Ivan Cibrario (Boca Raton : CRC Press, 2021)
"The focus of this book is on enabling real-time embedded software engineering while providing sufficient theoretical foundations and hardware background to understand the rationale for key decisions in RTOS and application design and implementation. All the authors of this book are experts in the academic field of real-time embedded systems. Two of the authors are primary open-source maintainers of the RTEMS software project"--
OCLC-licensed vendor bibliographic record.
Keywords: Embedded computer systems; Real-time data processing; Automatic control; COMPUTERS / General; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General